ROLE OF HUMAN RESOURCE MANAGEMENT IN ENHANCING WORKFORCE AGILITY AND RESILIENCE IN HEALTHCARE ORGANIZATIONS - Biswo Ranjan Mishra, S. L. Sobiya, R. Madhulaa, K. Suresh Kumar, Divya Jyoti Thakur, Esther Shalini L (South Eastern European Journal of Public Health, 2025)
The healthcare industry operates in an environment of constant change, driven by technological advancements, evolving patient expectations, regulatory updates, and global health crises. Workforce agility and resilience are critical factors for healthcare organizations to maintain operational efficiency and ensure high-quality patient care. Human Resource Management (HRM) plays a pivotal role in fostering these attributes through strategic talent acquisition, continuous training, performance management, and employee well-being initiatives. This paper explores how HRM practices contribute to workforce agility and resilience in healthcare settings. It examines key HRM strategies such as leadership development, employee engagement, and flexible work arrangements that support adaptability and sustainability. By implementing innovative HRM policies, healthcare organizations can enhance their capacity to respond effectively to emerging challenges while maintaining a motivated and competent workforce.